Geometric filters for protein–ligand complexes based on phenomenological molecular models - Sudakov, O.O.; Balinskyi, O.M.; Platonov, M.O.; Kovalskyy, D.B. (Вiopolymers and Cell, 2013)
Molecular docking is a widely used method of computer-aided drug design capable of accurate prediction of protein-ligand complex conformations. However, scoring functions used to estimate free energy of binding still lack accuracy. Aim. Development of computationally simple and rapid algorithms for ranking ligands based on docking results. Methods. Computational filters utilizing geometry of protein-ligand complex were designed. Efficiency of the filters was verified in a cross-docking study with QXP/Flo software using crystal structures of human serine proteases thrombin (F2) and factor Xa (F10) and two corresponding sets of known selective inhibitors. Results. Evaluation of filtering results in terms of ROC curves with varying filter threshold value has shown their efficiency. However, none of the filters outperformed QXP/Flo built-in scoring function Pi . Nevertheless, usage of the filters with optimized set of thresholds in combination with Pi achieved significant improvement in performance of ligand selection when compared to usage of Pi alone. Conclusions. The proposed geometric filters can be used as a complementary to traditional scoring functions in order to optimize ligand search performance and decrease usage of computational and human resources. Молекулярний докінг є широко застосовуваним обчислювальним методом пошуку лігандів біомолекул, здатним до достатньо точного передбачення конформацій комплексів білок–ліганд. У той же час скоринговим функціям, що використовують для оцінки сили зв’язування, бракує точності. Мета. Розробка обчислювально простих та швидких алгоритмів для вибору потенційних лігандів з комплексів, отриманих у результаті докінгу. Методи. Створено обчислювальні фільтри, засновані на геометричних співвідношеннях у комплексі білок–ліганд, ефективність яких перевірено крос-докінговим дослідженням із застосуванням кристалічних структур людських серинових протеаз тромбіна (F2) і фактора 10а (F10), а також двох відповідних наборів відомих селективних інгібіторів за допомогою програмного забезпечення QXP/Flo. Результати. Оцінено результати застосування фільтрів у термінах ROC-кривих із змінними пороговими значеннями та показано їхню ефективність. Проте жоден з фільтрів не перевершив за ефективністю вбудовану скорингову функцію Pi програми QXP/ Flo. Тим не менш, використання фільтрів з оптимізованими пороговими значеннями у комбінації з Pi дозволило значно збільшити ефективність порівняно із застосуванням лише Pi. Висновки. Розроблені геометричні фільтри можуть слугувати доповненням до традиційних скорингових функцій для оптимізації пошуку лігандів і зменшення залучення обчислювальних та люд- ських ресурсів. Молекулярный докинг – широко используемый вычислительный метод поиска лигандов биомолекул, способный довольно точно предсказывать конформацию комплекса белок–лиганд. В то же время скоринговые функции, используемые для оценки силы связывания, недостаточно точны. Цель. Разработка вычислительно простых и быстрых алгоритмов для выбора потенциальных лигандов из комплексов, полученных в результате докинга. Методы. Созданы вычислительные фильтры на основе геометрических соотношений в комплексе белок–лиганд, эффективность которых проверена кросс-докинговым исследованием c применением кристаллических структур человеческих сериновых протеаз тромбина (F2) и фактора 10а (F10), а также двух соответствующих наборов известных селективных ингибиторов с помощью программного обеспечения QXP/Flo. Результаты. Оценены результаты применения фильтров в терминах ROC-кривых с переменными пороговыми значениями и показана их эффективность. Однако ни один из фильтров не превзошел по эффективности встроенную скоринговую функцию Pi программы QXP/Flo. Тем не менее, использование фильтров с оптимизированными пороговыми значениями в комбинации с Pi позволило существенно увеличить эффективность в сравнении с применением только Pi. Выводы. Разработанные геометрические фильтры могут служить дополнением к традиционным скоринговым функциям для оптимизации поиска лигандов и уменьшения привлечения вычислительных и человеческих ресурсов.